Thermal oxidation–electroreduction modified 3D NiCu for efficient alkaline hydrogen evolution reaction. (23rd June 2021) - Zhou, Bo; Hu, Hanjun; Jiao, Zhiwei; Tang, Yang; Wan, Pingyu; Yuan, Qipeng; Hu, Qing; Yang, Xiao Jin
Abstract: The preparation of high-efficiency and low-cost electrocatalysts is vital to the development of green hydrogen energy. In this study, 3D NiCu electrodes with hierarchical micro-nano structure was constructed by a simple direct-write 3D printing technology and followed by the treatment of thermal oxidation - electroreduction steps. The composite structure of Cu NWs/Cu2 O and Ni/NiO in the prepared 3D NiCu promotes the dissociation of water and the conversion of hydrogen, and the special micro-nano structure displays a large active surface area. Therefore, the 3D NiCu exhibits a low overpotential of 70 mV to deliver a current density of 10 mA cm −2 . It demonstrates outstanding stability in the hydrogen evolution reaction experiment for 100 h in 1 M KOH. Overall, this research provides a pioneer of modified 3D printing to hydrogen production by water electrolysis. Graphical abstract: Image 1 Highlights: Bimetallic NiCu electrode was uniformly formed by direct-write 3D printing technology. Micro-nano structure was prepared through thermal oxidation – electroreduction. Prepared electrode show excellent HER performance in alkaline condition.